Developmental or Procedural Vena Cava Interruption and Venous Thromboembolism: A Review - Bikdeli, Behnood; Sadeghipour, Parham; Lou, Junyang; Bejjani, Antoine; Khairani, Candrika D.; Rashedi, Sina; Lookstein, Robert; Lansky, Alexandra; Vedantham, Suresh; Sobieszczyk, Piotr; Mena-Hurtado, Carlos; Aghayev, Ayaz; Henke, Peter; Mehdipoor, Ghazaleh; Tufano, Antonella; Chatterjee, Saurav; Middeldorp, Saskia; Wasan, Suman; Bashir, Riyaz; Lang, Irene M.; Shishehbor, Mehdi H.; Gerhard-Herman, Marie; Giri, Jay; Menard, Matthew T.; Parikh, Sahil A.; Mazzolai, Lucia; Moores, Lisa; Monreal, Manuel; Jimenez, David; Goldhaber, Samuel Z.; Krumholz, Harlan M.; Piazza, Gregory (Seminars in Thrombosis and Hemostasis, 2024)
The inferior vena cava (IVC) and superior vena cava are the main conduits of the systemic venous circulation into the right atrium. Developmental or procedural interruptions of vena cava might predispose to stasis and deep vein thrombosis (DVT) distal to the anomaly and may impact the subsequent rate of pulmonary embolism (PE). This study aimed to review the various etiologies of developmental or procedural vena cava interruption and their impact on venous thromboembolism. A systematic search was performed in PubMed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines per each clinical question. For management questions with no high-quality evidence and no mutual agreements between authors, Delphi methods were used. IVC agenesis is the most common form of congenital vena cava interruption, is associated with an increased risk of DVT, and should be suspected in young patients with unexpected extensive bilateral DVT. Surgical techniques for vena cava interruption (ligation, clipping, and plication) to prevent PE have been largely abandoned due to short-term procedural risks and long-term complications, although survivors of prior procedures are occasionally encountered. Vena cava filters are now the most commonly used method of procedural interruption, frequently placed in the infrarenal IVC. The most agreed-upon indication for vena cava filters is for patients with acute venous thromboembolism and coexisting contraindications to anticoagulation. Familiarity with different forms of vena cava interruption and their local and systemic adverse effects is important to minimize complications and thrombotic events.
Keywords: venous thromboembolism; deep vein thrombosis; pulmonary embolism; IVC agenesis; vena cava filters; IVC ligation